Effect Of Murottal Al-Quran Letter Asy-Syu'ara Therapy On Blood Pressure In Hypertension Patients - Mohammaad Shiddiqsuryadi; Mukhlish Hidayat, Mukhlish Hidayat; Husnul Mubarokal Muwanni, Husnul Mubarokal Muwanni; Siti Nur Hasina, Siti Nur Hasina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Hypertension is a major public health problem. There are two ways to treat high blood pressure: drug therapy and non-drug therapy. Treatment includes the use of antihypertensive drugs that have been shown to lower blood pressure. Meanwhile, non-drug treatments for high blood pressure include Murotal Al-Quran. The aim of this study was to analyze the effect of mulottal therapy verses 1 to 97 of Surah Asi-Shuara Al-Quran on the blood pressure of hypertensive patients in Poshandu in the Banyuanyar Community Health Center area. The research design used was a one group pre-post test design using a simple random sampling technique. The intervention took the form of offering Mulottar Al-Quran Surah Asi Shuara verses 1 to 97 for 15 minutes for three consecutive days. The total sample consisted of 41 hypertensive patients. The results of the Wilcoxon sign-rank test between pre and post test blood pressure in the Banyuan Yar Community Health Center work area showed = 0.002 and the comparative significance value = 0.05. Statistics = 0.002 < 0.05. The trial results showed that Murotar Al-Quran Surah As Shuara Therapy was effective on the blood pressure of elderly hypertensive patients in Poshandu in the Banyuanyar Community Health Center working area. In conclusion, Murottar Therapy according to the Al-Quran Surah Asi Shuara has been proven to be effective in reducing blood pressure in hypertensive patients. The suggestion is that hypertensive patients can use Al-Quran Surah Asi Shuara mulottal therapy to lower their blood pressure.